2023
DOI: 10.3390/antibiotics12060987
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical and Biological Characterization of Encapsulated Olive Leaf Extracts for Food Preservation

Abstract: Phenolic compounds in olive leaves have an excellent antioxidant activity and good antimicrobial properties. These bioactive molecules have beneficial properties for health, arousing great scientific and commercial interest. This study reports lyophilized olive leaf extracts (OLE) encapsulated by spray-drying using maltodextrins, maltodextrins–pectin and maltodextrins–gum Arabic as encapsulating agents. Lyophilized OLE were collected from two varieties cultivated in a harsh pedo-climatic conditions of the arid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 51 publications
0
1
1
Order By: Relevance
“…MC of encapsulated CPH powders rich in alkaloids found in this study (4.78 to 5.88%) is lower than that obtained from Andean blueberry juice using maltodextrin as a drying aid (4.3 to 8.6%), whereas a w of encapsulated CPH powders (0.46 to 0.51) is higher than that of encapsulated powders from Andean blueberry juice (0.27 to 0.52) [34]. The former work [35] also indicated that the best conditions for encapsulation of olive leaf extracts were obtained by combination of maltodextrins-pectin and maltodextrins-gum Arabic to form a hybrid coating material, which achieved an encapsulation e ciency over 75% and particle sizes between 9.1 to 10.8 µm. The WSI of powdered CPH extract rich in alkaloids in this study is compable to grape skin extract microencapsulated by freezedrying (85.96-88.0%) [8] but lower than that of encapsulated powders obtained by freeze-drying from Andean blueberry juice (91.1-94.6%).…”
Section: Resultscontrasting
confidence: 64%
“…MC of encapsulated CPH powders rich in alkaloids found in this study (4.78 to 5.88%) is lower than that obtained from Andean blueberry juice using maltodextrin as a drying aid (4.3 to 8.6%), whereas a w of encapsulated CPH powders (0.46 to 0.51) is higher than that of encapsulated powders from Andean blueberry juice (0.27 to 0.52) [34]. The former work [35] also indicated that the best conditions for encapsulation of olive leaf extracts were obtained by combination of maltodextrins-pectin and maltodextrins-gum Arabic to form a hybrid coating material, which achieved an encapsulation e ciency over 75% and particle sizes between 9.1 to 10.8 µm. The WSI of powdered CPH extract rich in alkaloids in this study is compable to grape skin extract microencapsulated by freezedrying (85.96-88.0%) [8] but lower than that of encapsulated powders obtained by freeze-drying from Andean blueberry juice (91.1-94.6%).…”
Section: Resultscontrasting
confidence: 64%
“…For instance, the addition of olive leaves extract in a chitosan-based edible film helped to prevent lipid oxidation, microbial growth, and texture changes in pork burgers . Within this framework, encapsulation of the active olive-based ingredients on the polymeric matrix enabled extended food shelf life through enhanced stabilization of phenolic compounds . Additionally, biobased and biodegradable polymers represent an eco-friendly approach to mitigate the environmental impact of plastic consumption, particularly for disposable products.…”
Section: Polyphenols Found In Olea Europaea Lmentioning
confidence: 99%